EMPOWERMENT OF YOUTH TO CREATE DIGITAL CONTENT AS A BRANDING OF RELIGIOUS TOURISM IN LENGKONG KYAI - Purwanto, Edi; Syarief, Rachman; Dawan, Anil; Sofia, Irma Paramita; Suprapto, Ratno (Universitas Bunda Mulia, 2022)
This Community Service activity is a follow-up to the results of previous research in Lengkong Kyai village, which is sandwiched between luxury housing in the BSD City area. The activity aims to provide training on content creation, infographics, or graphic design for digital promotional content, which suggests promoting the Raden Aria Wangsakara Cemetery as a religious tourism destination and cultural tourism. The methods of implementing the service are (1) Socialization on the importance of promoting the Lengkong Culture site, (2) Training on creating promotional content concepts, (3) Training on making infographics and designs, (4) Training on creating and managing promotional accounts, (5) Submission of design assets in the form of laptop, (6) Evaluation of program implementation and sustainability. The pre-test and post-test results showed an increase in the understanding of community service participants in the four counseling and training sessions provided. The benefits of this community service result are not only the ability of the community (participants) to create interesting content and graphic designs for the promotion of cultural sites as religious and cultural tourism destinations on social media, but they can use this ability for activities that have a positive impact on their economy. The increasing number of religious and cultural tourism visits to their villages will also positively impact the local community's economy.